Three-dimensional motion of shoulder complex during front crawl swimming - Du, T.; Yanai, T. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purposes of the study were to describe glenohumeral joint motion during front crawl swimming and to determine if the glenohumeral joint motion could be predicted by the humero-thoracic motion using linear regression model. Fourteen swimmers were asked to perform a resisted front crawl swimming. Three-dimensional motions of shoulder complex were measured with an electromagnetic tracking devise. The results showed that humerus and scapula did not move in a set ratio during front crawl swimming and the glenohumeral joint motion could not be predicted accurately from the humero-thoracic motion. A characteristic movement pattern was observed in the catch phase in which the humerus moved caudally behind the scapular plane while moving in front of the torso. This movement pattern may facilitate internal rotation of the shoulder to execute the catch and pull vigorously.